2011
DOI: 10.2967/jnumed.110.084731
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/MRI Can Be Used to Identify Injured Peripheral Nerves in a Model of Neuropathic Pain

Abstract: We demonstrated increased 18 F-FDG uptake in injured peripheral nerves in a model of neuropathic pain using small-animal PET/MRI. Methods: A neuropathic pain model in rats was created by spared-nerve injury of the left sciatic nerve. Shamoperated rats without nerve injury were used as a control. The presence of pain was confirmed by testing for allodynia. Sequential small-animal 18 F-FDG PET and MRI scans of the thighs were obtained and coregistered. Autoradiography was performed on harvested nerves and muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 14 publications
0
37
0
1
Order By: Relevance
“…Most of the current PET research in the peripheral nervous system involves evaluating peripheral nerve sheath tumors with very limited use in assessing injured peripheral nerves [Ferner et al, 2008; Lucas et al, 1998; Behera et al, 2011; Ferner et al, 2000]. PET imaging has shown significant utility in detecting nerve sheath tumors as well as in other fields, and its value in evaluating peripheral nerve metabolism and nerve injury warrants further investigation [Behera et al, 2011; Tatsumi et al, 2011; Osborn, and Jaffer, 2009]. The primary marker of nerve injury in 18 F-FDG-PET is the increased uptake of 18 F-FDG by damaged nerves, which corresponds with higher levels of metabolic activity.…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the current PET research in the peripheral nervous system involves evaluating peripheral nerve sheath tumors with very limited use in assessing injured peripheral nerves [Ferner et al, 2008; Lucas et al, 1998; Behera et al, 2011; Ferner et al, 2000]. PET imaging has shown significant utility in detecting nerve sheath tumors as well as in other fields, and its value in evaluating peripheral nerve metabolism and nerve injury warrants further investigation [Behera et al, 2011; Tatsumi et al, 2011; Osborn, and Jaffer, 2009]. The primary marker of nerve injury in 18 F-FDG-PET is the increased uptake of 18 F-FDG by damaged nerves, which corresponds with higher levels of metabolic activity.…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…The primary marker of nerve injury in 18 F-FDG-PET is the increased uptake of 18 F-FDG by damaged nerves, which corresponds with higher levels of metabolic activity. As injured neurons maintain higher rates of neuron firing, the difference in the γ photon emissions between injured and uninjured nerves can provide opportunities to locate and assess injured nerves [Behera et al, 2011]. Although current PET imaging of peripheral nerves uses metabolism to characterize injury, future research should seek to develop agents other than 18 F-FDG that specifically target injured nerves rather than only tissues with high metabolism.…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
See 1 more Smart Citation
“…PET/MRI offers to combine molecular information to localize neuropathic pain with MRI which is able to provide high-resolution visualization of anatomical abnormalities (107). MRI in non-oncologic musculoskeletal applications.…”
Section: Challenges and Alternative Imaging Methodsmentioning
confidence: 99%
“…FDG PET imaging can image the increased glucose metabolism utilized by inflamed or overactive neurons as a marker of neural activity. Studies in a rat model that used unilateral injury to induce neuropathic limb pain showed increased FDG uptake in injured nerves, but no increase in FDG uptake in the contralateral limb or in control asymptomatic animals ( Figure 4) (107). Additionally, in a human subject presenting with progressive difficulty walking, increased FDG uptake was observed in his lower spinal cord and sciatic nerves (108).…”
Section: Pain Generators and Peripheral Nerve Imagingmentioning
confidence: 98%